Finding the X Factor: Counter-frames, Political Opinion Formation, and Agency in Reconciliation Efforts for Indonesia’s 1965 Anti-Communism Purge Victims - Putri, Adelia Anjani (JURNAL KOMUNIKASI INDONESIA, 2017)
Indonesians are taught by the government that communism is a devil trying to rip the country’s democratic and religious values. The propaganda started with a ‘coup attempt’ perpetrated by the Indonesian Communist Party (PKI) on September 30, 1965 that left several army high ranking officers killed. The putsch then justified a state-supported genocide throughout the country that claimed up to 1.5 million of suspected PKI supporters. Whether the coup attempt happened and who masterminded the tragedy has remained unanswered, and the victims have yet to find justice until now. Movements to demand truth, econciliation and the state’s formal apology for this travesty have been going on for years without concrete results. Despite increasing media coverage and effort to provide another side of the story, public opinions and attitude are relatively unchanged. This research aims to find how counter-frames of the social movements affect people’spolitical opinion formation process; whether counter-frames can surpass existing common knowledge; and whether human agency can be formed in this specific case. It is discovered that counter-frames can affect one’s understanding and stance in various degrees depending on their initial proximity, level of interest, and knowledge about the issue. This research also finds that among Collective Action Frames, agency is the most influential source of injustice and the party regarded as the enemy will only open a new discourse and change public opinion but are not enough to make people act. Publik Indonesia diajari oleh pemerintah bahwa komunisme adalah iblis yang mencoba merobek nilai-nilai demokrasi dan agama. Propaganda dimulai dengan sebuah ‘usaha kudeta’ oleh Partai Komunis Indonesia (PKI) pada tanggal 30 September 1965 yang membunuh beberapa petinggi militer Perstiwa tersebut Putsch kemudian menjadi pembenar genosida yang didukung pemerintah di seluruh negeri yang menewaskan hingga 1,5 juta orang yang dituh sebagai pendukung PKI. Bagaimana upaya kudeta tersebut terjadi, siapa yang berada di balik tragedi belum terjawab, dan korban belum menemukan keadilan sampai sekarang. Gerakan menuntut kebenaran, rekonsiliasi, dan permintaan maaf resmi dari negara untuk peristiwa ini telah berlangsung bertahun-tahun tanpa hasil yang nyata. Meskipun liputan dan upaya media meningkat untuk memberikan sisi lain dari cerita tersebut, opini publik dan sikap relatif tidak berubah. Tujuan penelitian ini mengetahui bagaimana kontra-frame gerakan sosial mempengaruhi proses pembentukan opini politik masyarakat; apakah counter-frame bisa melampaui pengetahuan umum yang ada; dan apakah agen manusia dapat dibentuk dalam kasus khusus ini. Hasil penelitian menemukan, kontra-frame dapat mempengaruhi pemahaman dan pendirian seseorang dalam berbagai tingkat tergantung pada jarak awal, tingkat kepentingan, dan pengetahuan mereka mengenai masalah ini. Penelitian ini juga menemukan bahwa di antara Collective Action Frames, agensi adalah yang paling berpengaruh sebagai sumber ketidakadilan dan pihak yang dipandang bersalah (enemy) hanya akan membuka wacana baru dan mengubah opini publik namun tidak cukup untuk membaut orang bertindak.